2021
DOI: 10.3390/s21124230
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Reflectance Spectroscopy for Predicting the Phospholipid Fraction and the Total Fatty Acid Composition of Freeze-Dried Beef

Abstract: Research on fatty acids (FA) is important because their intake is related to human health. NIRS can be a useful tool to estimate the FA of beef but due to the high moisture and the high absorbance of water makes it difficult to calibrate the analyses. This work evaluated near-infrared reflectance spectroscopy as a tool to assess the total fatty acid composition and the phospholipid fraction of fatty acids of beef using freeze-dried meat. An average of 22 unrelated pure breed young bulls from 15 European breeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(113 reference statements)
1
5
0
Order By: Relevance
“…The results (shown in Table 6) agree with those found by other authors for the Merino breed [41][42][43][44]. We found an effect of the type of animal in 23 of the 41 fatty acids detected and, in general, the content of almost all of the fatty acids was higher in ewes' meat than in lambs' meat, probably due to the higher fat content of the former [45]. Numerous studies have indicated that increased intramuscular fat content is associated with an increase in total saturated fatty acids and a decrease in polyunsaturated fatty acids [46].…”
Section: Fatty Acid Profilesupporting
confidence: 91%
“…The results (shown in Table 6) agree with those found by other authors for the Merino breed [41][42][43][44]. We found an effect of the type of animal in 23 of the 41 fatty acids detected and, in general, the content of almost all of the fatty acids was higher in ewes' meat than in lambs' meat, probably due to the higher fat content of the former [45]. Numerous studies have indicated that increased intramuscular fat content is associated with an increase in total saturated fatty acids and a decrease in polyunsaturated fatty acids [46].…”
Section: Fatty Acid Profilesupporting
confidence: 91%
“…A significant number of spectra peaks were detected at 1454 nm (combination of C-H stretching and first overtone stretching) and at 1930 nm (combination of N-H stretching and O-H stretching), mostly associated with protein, water, sugar, and starch concentrations [ 80 , 81 ]. The second overtone of C-H stretching at 1205 nm, and the first overtone of C-H stretching between 1727 and 1797 nm are usually associated with fat and fatty acid content [ 82 , 83 ]. The predictability of fat content in living mealworm larvae is very good, but it could probably be improved by creating a larger variety of data for fat content within the calibration, as other studies have shown if more data points are available, a higher model performance is reached [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the freeze drying and grinding of samples is more expensive and labour intensive than analysing samples on a fresh basis, it is a preparation method already required by many wet chemistry assays carried out by researchers (AOAC, 2006, 2012). It has also been shown to improve the accuracy of NIRS predictions over scans performed on a fresh meat (Prieto et al ., 2017; Coombs et al ., 2021), as it eliminates problems such as water banding and sample heterogeneity (Prieto et al ., 2017; Ripoll et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%